2013
DOI: 10.1159/000354577
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endoscopic Mucosal Resection in Patients with Low-Grade Intraepithelial Dysplasia of Esophageal Squamous Cells

Abstract: Background: This study evaluated the effects of endoscopic mucosal resection (EMR) on patients with low-grade intraepithelial dysplasia (LGD) of the esophageal squamous cells. Methods: A randomized study recruited 128 LGD patients. These patients were randomly divided into treatment and control groups after the preoperative examination. The treatment group was composed of 63 LGD cases who received EMR. The control group included 65 LGD cases that were not treated with EMR. Clinical interviews and endoscopy wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…It has been reported that the progression of esophageal mucosa generally progresses through the stages of normal epithelium, mild atypical hyperplasia, moderate atypical hyperplasia, severe atypical hyperplasia, carcinoma in situ, invasive carcinoma, etc [ 21 ]. Although esophageal dysplasia does not require immediate endoscopic resection, surveillance should be maintained because of the potential risk of early esophageal cancer or precancerous lesions[ 22 - 24 ]. Early treatment of esophageal mucosal lesions is helpful for preventing progression to esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the progression of esophageal mucosa generally progresses through the stages of normal epithelium, mild atypical hyperplasia, moderate atypical hyperplasia, severe atypical hyperplasia, carcinoma in situ, invasive carcinoma, etc [ 21 ]. Although esophageal dysplasia does not require immediate endoscopic resection, surveillance should be maintained because of the potential risk of early esophageal cancer or precancerous lesions[ 22 - 24 ]. Early treatment of esophageal mucosal lesions is helpful for preventing progression to esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%